Modul digital layanan klasikal melalui platform zedemy untuk meminimalisir perilaku cyberbullying - Hendro Yulius Suryo Putro; Ali Rachman; Muhammad Andri Setiawan; Muhammad Pahri (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2022)
The use of devices that should be intended to support learning activities, it turns out that students can try various access to social media which can unwittingly increase cyberbullying. The classical services of School Counselor are also required to be adaptive to technology. However, the classic School Counselor service module is less attractive and rigid. The purpose of this study is to develop an integrated module with social media that is used as a classic Guidance and Counseling teacher service in Banjar Regency, South Kalimantan through the zedemy platform, which is expected to minimize cyberbullying. Research design using Research and Development (R&D) ADDIE model. Collecting data using Focus Group Discussion, and Likert scale questionnaire. The instrument used is the instrument of material, media and user feasibility. Data analysis was carried out descriptively to determine the characteristics of the distribution of respondents, then the Kendall's W concordance test was carried out to determine consistency and assessment.Expert tests are carried out by material experts, media experts and users. Based on the research, the material and media expert's assessment showed very good criteria, no revision needed. User ratings by Counselor School also showed very good criteria, no need for revision. So it can be concluded that the classical service digital module through the zedemy platform has met the criteria for being suitable for use as a classical service medium to minimize cyberbullying.